Drainage of middle lobe vein into anomalous right lower lobe vein: management during thoracoscopic lobectomy. Issue 5 (5th May 2020) - Amore, Dario; Saglia, Alessandro; Casazza, Dino; Valente, Tullio; Imitazione, Pasquale; Curcio, Carlo
Abstract: Variations in pulmonary venous anatomy should not be underestimated by thoracic surgeons prior to or during major lung resections in order to avoid serious surgical complications. Here, we report a case of middle lobe vein draining into a right inferior lobar vein formed by two anomalous trunks lying on the superior surface of the common basal bronchus: in such instance, to avoid compromising the middle lobe vein drainage during a thoracoscopic right lower lobectomy, the two main tributaries of the lower lobe vein were individually identified and dissected peripherally from the anterior aspect after division of the major fissure. A careful hilar dissection and a precise surgical strategy can help surgeons perform correct procedures in presence of pulmonary vascular anomalies. Abstract : Here, we report a case of middle lobe vein draining into a right inferior lobar vein formed by two anomalous trunks lying on the superior surface of the common basal bronchus: in such instance, to avoid compromising the middle lobe vein drainage during a thoracoscopic right lower lobectomy, the two main tributaries of the lower lobe vein were individually identified and dissected peripherally from the anterior aspect after division of the major fissure. A careful hilar dissection and a precise surgical strategy can help surgeons perform correct procedures in presence of pulmonary vascular anomalies.